1992
DOI: 10.1254/jjp.59.159
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Antinephritic Effect of Plant Components (4): Reduction of Protein Excretion by Berberine and Coptisine in Rats with Original-Type Anti-GBM Nephritis

Abstract: -The present study was conducted to investigate the antinephritic effects of berberine and coptisine, which are contained in Coptidis rhizoma, on original-type anti-GBM nephritis in rats. Ber berine and coptisine at the doses of 0.5, 1.0 and 5.0 mg/kg/day, i.p. were effective in inhibiting urinary protein excretion, elevation of serum cholesterol and creatinine contents as well as glomerular histo pathological changes. In addition, berberine at 20 mg/kg/day, p.o. also inhibited urinary protein excre tion throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
1
7
1
1
Order By: Relevance
“…Reductions of plasma TAG by BBR were also observed in other studies in rats with diabetes and nephritis [42,43,47]. Results from several in vitro studies have demonstrated that BBR decreases TAG levels through regulating fatty acid metabolism toward the downregulation of adipogenesis [51][52][53].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Reductions of plasma TAG by BBR were also observed in other studies in rats with diabetes and nephritis [42,43,47]. Results from several in vitro studies have demonstrated that BBR decreases TAG levels through regulating fatty acid metabolism toward the downregulation of adipogenesis [51][52][53].…”
Section: Discussionsupporting
confidence: 66%
“…This discrepancy may have resulted from the differences in the diet composition, especially dietary cholesterol and fat levels, bile acid supplementation, and the time of BBR administration between the present study and previous studies [13,26,42,43]. It could also be due to the differences in cholesterol metabolism between humans and animal species [44][45][46].…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In particular, the major medically important isoquinoline alkaloid, berberine, has been extensively studied [1][2][3][4][5][6][7][8][9] and recently reported to display beneficial effects in the treatment of diabetes, obesity and hyperlipidemia, [10][11][12] while both coptisine and palmatine have been reported to exhibit a limited number of biological activities compared with berberine. [13][14][15][16][17][18] These three isoquinoline alkaloids possess the same tetracyclic structure but differ in the nature of the substituents on the benzo ring, comprising methylene dioxy and/or dimethoxy substituents (Fig. 1).…”
mentioning
confidence: 99%